2020
DOI: 10.1111/gbb.12647
|View full text |Cite
|
Sign up to set email alerts
|

Using a mouse model to gain insights into developmental coordination disorder

Abstract: Motor impairments are a common feature of many neurodevelopmental disorders; in fact, over 50% of children with Attentional Deficit Hyperactivity Disorder or Autism Spectrum Disorder may have a co‐occurring diagnosis of developmental coordination disorder (DCD). DCD is a neurodevelopmental disorder of unknown etiology that affects motor coordination and learning, significantly impacting a child's ability to carry out everyday activities. Animal models play an important role in scientific investigation of behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 71 publications
(160 reference statements)
0
12
0
Order By: Relevance
“…The cerebellum’s key role in co-ordinated behaviours, postural control, and motor learning point to this structure underlying DCD. In support this hypothesis, Gill et al (2020) and Zwicker et al (2011) found structural and functional abnormalities in the cerebellum of children with DCD. Additionally, there is an indication that DCD has an underlying genetic component due to its high heritability.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The cerebellum’s key role in co-ordinated behaviours, postural control, and motor learning point to this structure underlying DCD. In support this hypothesis, Gill et al (2020) and Zwicker et al (2011) found structural and functional abnormalities in the cerebellum of children with DCD. Additionally, there is an indication that DCD has an underlying genetic component due to its high heritability.…”
Section: Introductionmentioning
confidence: 62%
“…Procedures: Behavioural Testing Detailed information on the study timeline is available in Figure 1 and rationale and procedural details for the behavioural tasks are outlined in Gill et al (2020). This paper focuses on the first third and last phases of the study, as outlined in Figure 1.…”
Section: Selection Of Bxd Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 10 BXD 1, BXD15, BXD27, BXD28, and BXD40 were selected due to their variation in cerebellar volume. 9…”
Section: Methodsmentioning
confidence: 99%
“…To capture the motor variability seen in BXD RI mice, we devised a battery of motor behavior tasks (Figure 1) to mimic the motor deficits observed in human DCD (see Gill et al 9 for details). Using this approach, we can begin to identify candidate regions of chromosomes that harbor genes that underlie the behaviors of interest in DCD using Quantitative Trait Loci (QTL) analysis.…”
Section: Introductionmentioning
confidence: 99%